Assessment of cardiorespiratory parameters in neuropediatric patients in a public institution in the city of Teresina, State of Piauí, Brazil (Research, Society and Development, 2025)
Neurological rehabilitation consists of a sensorimotor learning process based on intensive and task-oriented practice. In this sense, due to the diversity of neurological disorders, a comprehensive approach to the individual is necessary, therefore, monitoring heart rate and peripheral oxygen saturation parameters is essential to ensure the safety of therapeutic management. The objective of the study was to analyze the safety of physiotherapeutic management on heart rate and peripheral oxygen saturation parameters, in addition to the socioeconomic profile in children with neurological disorders, treated by a public institution in Teresina, Piauí. The study sample consisted of 13 children aged between 0 and 8 years old. Data collection took place in March and April 2025, through a specific form, where heart rate and peripheral oxygen saturation data and socioeconomic profile were recorded. Peripheral oxygen saturation and heart rate were measured using a G-tech oximeter before and immediately after the end of the treatment. The treatments lasted an average of 50 minutes and the interventions used were soft tissue release, joint mobilization, active and active-assisted exercises, and sensorimotor stimulation. The results showed that the physiological parameters evaluated did not present statistically significant differences, and that low socioeconomic states was predominant. Therefore, the physiotherapy treatment offered at the evaluated Public Institution proved to be safe, causing no changes in Heart Rate and peripheral oxygen saturation.